Estudo teórico da influência de um meio solvente na interação de aminoácidos com um nanotubo de carbono - Anversa, Jonas (2010)
In this work we use the Density Functional Theory (DFT) to analyze the influence of a water environment in the interaction between amino acids and a semiconductor carbon nanotube (CNT). To the study of the interaction in vacuum we use both an ab initio and a parameterized tight-binding method. To the study of the same interactions in water we performed finite temperature (300 K) molecular dynamics calculations, using the parameterized tight-binding method. The selected amino acids have different hydrophobicity and polarity indexes. Our study shows that for the neutral amino acids, a direct relationship between the variation in the bonding distances and the hydrophobicity indexes when changing from vacuum to water environments, with the hydrophobic (hydrophilic) amino acids getting nearer (farther) of the carbon nanotube. The change in the binding energies, when going from the vacuum to the water environments, shows an inverse relationship with the polarity, with the amino acids that have more polar (nonpolar) side chains showing lower (greater) variations in the binding energies. We also analyze the variations in the binding energies in vacuum and water for the neutral and zwitterionic forms of glicine. We show that the zwitterionic form is more stable in the polar environment of water, whereas the neutral form is more stable in vacuum.